Lulu2 regulates the circumferential actomyosin tensile system in epithelial cells through p114RhoGEF - Nakajima, Hiroyuki (The Rockefeller University Press, 2011)
Myosin II–driven mechanical forces control epithelial cell shape and morphogenesis. In particular, the circumferential actomyosin belt, which is located along apical cell–cell junctions, regulates many cellular processes. Despite its importance, the molecular mechanisms regulating the belt are not fully understood. In this paper, we characterize Lulu2, a FERM (4.1 protein, ezrin, radixin, moesin) domain–containing molecule homologous to Drosophila melanogaster Yurt, as an important regulator. In epithelial cells, Lulu2 is localized along apical cell–cell boundaries, and Lulu2 depletion by ribonucleic acid interference results in disorganization of the circumferential actomyosin belt. In its regulation of the belt, Lulu2 interacts with and activates p114RhoGEF, a Rho-specific guanine nucleotide exchanging factor (GEF), at apical cell–cell junctions. This interaction is negatively regulated via phosphorylation events in the FERM-adjacent domain of Lulu2 catalyzed by atypical protein kinase C. We further found that Patj, an apical cell polarity regulator, recruits p114RhoGEF to apical cell–cell boundaries via PDZ (PSD-95/Dlg/ZO-1) domain–mediated interaction. These findings therefore reveal a novel molecular system regulating the circumferential actomyosin belt in epithelial cells.